2009
DOI: 10.1242/dmm.002535
|View full text |Cite
|
Sign up to set email alerts
|

A conditional mouse model for human MUC1-positive endometriosis shows the presence of anti-MUC1 antibodies and Foxp3+ regulatory T cells

Abstract: SUMMARYEndometriosis is defined by the presence of tissue implants resembling endometrial glands outside of the uterus, at ectopic sites, frequently on the ovarian surface. The ectopic lesions are often invasive, resistant to therapy, and may predispose to endometrioid and clear cell ovarian tumors. The complex mechanisms leading to chronic endometriosis are mediated partly by impaired immune surveillance in the host. Although innate immunity has been addressed previously, the response of adaptive immune effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 57 publications
6
39
0
Order By: Relevance
“…No histological modifications of the ipsilateral oviduct and uterine horn were observed, confirming that intrabursal AdCre injections remain anatomically confined, as previously demonstrated by us and others using reporter gene experiments. 9,34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No histological modifications of the ipsilateral oviduct and uterine horn were observed, confirming that intrabursal AdCre injections remain anatomically confined, as previously demonstrated by us and others using reporter gene experiments. 9,34 …”
Section: Resultsmentioning
confidence: 99%
“…The only two existing preclinical cancer models for de novo tumors expressing MUC1 as self are for colon and pancreatic adenocarcinomas. 22,45,46 We describe here the first preclinical ovarian tumor model, which expresses human MUC1 antigen as a self molecule, using triple Tg MUC1KrasPten mice that carry the previously reported, loxP-engineered Kras and Pten loci, 9,34 while co-expressing MUC1 antigen, driven by the endogenous mucin 1 promoter. 33 The tumors develop at the primary site, metastasize throughout the peritoneal cavity and on the diaphragm and are accompanied by increased circulating MUC1 levels, replicating more closely the human disease.…”
Section: Discussionmentioning
confidence: 97%
“…Tregs are characterized by FOXP3 and produce IL-10 and TGF- β , suppressing activation of the immune system and thereby maintaining immune system homeostasis and tolerance to self-antigens [7882]. A mouse model study [83] reported in late-stage of the disease a switch toward Th2 and Treg cell profiles, with an overrecruitment of Foxp3 + CD4 + Tregs in the draining lymph nodes. This is congruent with our previous reported results [34].…”
Section: Immune Disturbance Of the Peritoneal Microenvironmentmentioning
confidence: 99%
“…To further explore this mechanism, we employed triple transgenic mice that progress to EAOC closely mirroring the human disease. 6,7 Using this preclinical model, we demonstrated that complement upregulation in epithelial cells occurs early in carcinogenesis.…”
Section: Introductionmentioning
confidence: 94%